2018
DOI: 10.1093/annonc/mdy117
|View full text |Cite
|
Sign up to set email alerts
|

Anti-infective vaccination strategies in patients with hematologic malignancies or solid tumors—Guideline of the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO)

Abstract: Infectious complications are a significant cause of morbidity and mortality in patients with malignancies specifically when receiving anticancer treatments. Prevention of infection through vaccines is an important aspect of clinical care of cancer patients. Immunocompromising effects of the underlying disease as well as of antineoplastic therapies need to be considered when devising vaccination strategies. This guideline provides clinical recommendations on vaccine use in cancer patients including autologous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 130 publications
(170 reference statements)
2
73
0
16
Order By: Relevance
“…Most centers start to vaccinate children with inactivated vaccines 3 months after autologous HSCT, which is also recommended by current guidelines [10,17,18] (▶ Table 2). In contrast, we found a wide variation regarding the administration of live-attenuated vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Most centers start to vaccinate children with inactivated vaccines 3 months after autologous HSCT, which is also recommended by current guidelines [10,17,18] (▶ Table 2). In contrast, we found a wide variation regarding the administration of live-attenuated vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The 13-valent conjugate vaccine, however, comprises only about 30% of pneumococcal infections in adults, in contrast the 23-valent polysaccharide inoculum about 60-70%. Therefore, the sequential vaccination with both inocula conveys the best protection against pneumococcal infections at the moment [3][4][5][6][7][8].…”
Section: Individuals With Immune-suppression Advanced Liver Cirrhosimentioning
confidence: 99%
“…The recommendations on vaccination with anti-CD20 therapies could be extrapolated to anti-CD19 targeted agents such as blinatumomab. 28 Live vaccines for infants born from mothers on CD19 targeted agents should be postponed until B cell recovery. 105 Anti-CD20 monoclonal antibodies Tetanus immunoglobulin should be administered in patients with contaminated wounds who have received anti-CD20 monoclonal antibodies in the past six months.…”
Section: Cd19-targeted Agentsmentioning
confidence: 99%
“…98 Administration of second booster dose of inactivated influenza vaccine is associated with superior immunity response. 28 Non-immunized patients who are candidates for R-CHOP therapy should complete HBV vaccines ≥ 4 weeks prior to the initiation of rituximab. 14 Case reports have demonstrated that immunization of infants born from mothers on rituximab therapy up to the third trimester was not attenuated.…”
Section: Cd19-targeted Agentsmentioning
confidence: 99%